Testing Alternative Hydroponic Nutrition of Wick System on Vegetable Growth Planted in Limited Land - Hayati, Rita; Armadi, Yukiman; Yusnaweti, Yusnaweti; Feni, Rita; Asfaruddin, Asfaruddin; Ariyani, Farida; Kesumawati, Neti; Suzanna, Eka; Sarina, Sarina (Journal La Lifesci, 2024)
This research aims to obtain suitable alternative nutrients for vegetable cultivation using the Hydroponic Wick System so that the production costs of hydroponic cultivation can be cheaper and more affordable. The research was conducted in the Tebeng area, Ratu Agung Kodya Bengkulu, at an elevation of 50 meters above sea level. The research method used was a Randomized Block Design with a Factorial pattern (RAKF). The first factor had 3 levels of vegetable types: kailan (S1), caisim (S2), and pakcoy (S3). The second factor had 3 levels of nutrients: AB Mix 100% (N1), alternative 100% (N2), and ABMix 50% + alternative 50% (N3). Thus, there were 9 treatment combinations with 3 replications. The results of the research showed that the plant height, number of leaves, wet weight, and dry weight of plants using Alternative Nutrients for kailan, caisim, and pakcoy vegetables significantly influenced the use of AB Mix nutrients, Alternative Nutrients, and the mixture of both nutrients when grown using the Hydroponic Wick system. The best results were achieved using alternative nutrients. This was evident from the tallest plant height at harvest, which was 34.20 grams at 42 days after planting (HST), 16.62 leaves, 142.69 grams wet weight, and 7.60 grams dry weight. These results were significantly better compared to using other nutrients, offering a potential solution to the high costs of hydroponic cultivation due to the expensive price and limited availability of AB Mix nutrients, especially in the region.